2017
DOI: 10.1111/acv.12334
|View full text |Cite
|
Sign up to set email alerts
|

‘The early bird catches the nest’: possible competition between scops owls and ring‐necked parakeets

Abstract: Competition for critical resources is one of the key mechanisms through which invasive species impact on native communities. Among birds, the widely introduced ring-necked parakeet Psittacula krameri locally affects cavity-nesting communities through competition for suitable tree cavities, although it remains unclear to what extent such competition translates into population declines of native species. Here, we studied the potential for nest site competition between ring-necked parakeets and the native scops o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 50 publications
(79 reference statements)
0
16
0
Order By: Relevance
“…Although there are concerns that mites may be vectors for diseases among parrots, most feather mites are considered ecto-commensals and feed on the oils produced by the birds (Blanco et al, 2001). Competition for nesting cavities is a major cause of concern because there are native species which depend on this scarce resource, and psittacine secondary cavity nesters can be aggressive competitors (Snyder et al, 2007;Strubbe & Matthysen, 2009a;Orchan et al, 2012;Mori et al, 2017). Currently, populations of non-indigenous cavity nesters (e.g., Amazona spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although there are concerns that mites may be vectors for diseases among parrots, most feather mites are considered ecto-commensals and feed on the oils produced by the birds (Blanco et al, 2001). Competition for nesting cavities is a major cause of concern because there are native species which depend on this scarce resource, and psittacine secondary cavity nesters can be aggressive competitors (Snyder et al, 2007;Strubbe & Matthysen, 2009a;Orchan et al, 2012;Mori et al, 2017). Currently, populations of non-indigenous cavity nesters (e.g., Amazona spp.…”
Section: Discussionmentioning
confidence: 99%
“…The ring-necked parakeet in the study area A pair of RNP was first observed in Follonica in 1999 and the population peaked at 30-35 individuals in 2016 (Pârâu et al, 2016;Mori et al, 2017). In winter 2017, a group of eight long-eared owls established a roost at a distance of about 300 m from the parakeet roost.…”
Section: Study Areamentioning
confidence: 99%
“…The mean annual temperature was 16.8 ºC, with annual precipitation of 650-700 mm (Mori et al, 2017). This urban area is surrounded by farmland, mainly cereal and sunflower fields) and wide coastal pinewood forests with Pinus pinea (Mori et al, 2017). The first control site was located in the southern peripheral area of the city of Grosseto (42.77 ºN, 11.13 ºE: 14-18 m a.s.l.…”
Section: Study Areamentioning
confidence: 99%
See 1 more Smart Citation
“…Snyder, Wieley & Kepler, 2007;Strubbe & Matthysen, 2009a;Orchan et al, 2012;Mori et al, 2017).However, populations of cavity nesters (e.g., Amazona spp and rose-ringed parakeets) are relatively low, and the most successful psittacine species in Puerto Rico build their own nests. Finally, based on the distribution of Amazona spp.…”
mentioning
confidence: 99%